Traumatic surdural hygroma - Five cases with changed density and spontaneous resolution - Zanini, Marco Antonio [UNESP]; Resende, Luiz Antonio de Lima [UNESP]; Freitas, Carlos Clayton Macedo de [UNESP]; Yamashita, Seizo [UNESP] (Associação Arquivos de Neuro- Psiquiatria, 2007)
Thirty-four consecutive adult patients with subdural traumatic hygroma were analysed for clinical evolution, serial computed tomography scan (CT), and magnetic resonance imaging (MRI) over a period of several months. Five of the patients presented CT scan and MRI evolution data showing increasing density over a period of 11 days to 6 months post trauma. In these five patients, final clinical and CT scan data were benign, with complete spontaneous resolution. Descriptions in literature of evolving traumatic subdural hygroma have presented CT scan density modifications changing into chronic subdural hematoma. Our patients show another possibility, density transformation, which sometimes show as subdural hematoma in CT scan and MRI, but with final evolution where clinical condition and CT scan return to normal.
Keywords: traumatic subdural hygroma; evolution; head injury; CT scan